The Influence Of Work Discipline And Physical Work Environment On Employee Performance At PT. Inkaprima Jaya Jakarta Selatan - Afriansyah, Andika; Prabowo, Budhi (Transforma Jurnal Manajemen, 2025)
The aim of this research is to determine the influence of work discipline and work environment on the performance of PT Inkaprima Jaya South Jakarta employees, both partially and simultaneously. The research method used is a quantitative method with an deskriptif approach. The sampling technique used was saturated sampling technique, namely using a sample of 75 respondents from the entire population. The data analysis techniques used are instrument testing, classical assumption testing, linear regression analysis, correlation coefficient analysis, determination coefficient analysis, hypothesis testing. This is proven by the results of the work discipline hypothesis test, which obtained a tcount value of 4,763 > ttable 1,293 and was strengthened by the ? value < Sig.0.05 or a significance value < 0.05 (0.000 < 0.05). The work environment obtained a tcount value of 0.778 > ttable 1,293 and is strengthened by the ? value < Sig.0.05 or significance value < 0.05 (0.439 > 0.05). The research results of work discipline and work environment simultaneously have a positive and insignificant effect on employee performance at PT Inkaprima Jaya South Jakarta, shown by the multiple linear regression equation Y = 19.557 + 0.427X1 + 0.012X2. This is proven by the results of simultaneous hypothesis testing obtained by the Fcount value (11,200 > Ftable 3.12) and reinforced by the significance value < 0.00 (0.000 < 0.05). The results of the coefficient of determination test for work discipline and work environment variables have an influence of 23.7% on employee performance at PT Inkaprima Jaya South Jakarta. Thus H01 is accepted and H3 is rejected. This means that it is proven that there is a simultaneous insignificant influence between work discipline (X1) work environment (X2) on employee performance (Y)